Considerações teológicas e antropológicas a partir da relação entre razão e Deus em Kant - Klabunde, Rafael (Vox Scripturae - Revista Teológica Internacional, 2012)
This article presents an approach about the contribution of Immanuel Kant’s thought regarding the human being and God, from the first chapter of his work entitled Streit der Fakultäten (Conflict of the Faculties). Traces of Kant’s life are presented and the context in which he lived, the Illuminism, and also about his though in relation to knowledge and moral. After the approach about the work cited above, conclusions regarding who is the human being and which is the importance and function of God according to Kant are shown. The human being is rational and searches to understand everything inside the relation of cause and effect, however not everything can be rationally understood; for example God. The relation between cause and effect needs to be abandoned to live in society in a respectful way, and for this God is necessary. According to Kant, God becomes morally important for the human being.